Forms of care. Ethics of caring in the healthcare context - Mancini, Elena (Medicina e Morale, 2025)
To have placed a special emphasis on the rights of patients who are granted autonomy regarding decisions about their own bodies has been the main achievement of a medicine that has finally overcome the paternalistic model of the doctor-patient relationship, even if the way to exercise that autonomy is not always easy. Often, however, illness profoundly changes the context, many ordinary references lose relevance, the meaning of relationships changes profoundly, and in some cases the sense of reality itself has little relevance. The concrete possibility of death creates an entirely specific temporal dimension, in which many choices no longer have a reason for being and others on the contrary become urgent. Traditional ethics based on reciprocity of relationships, evaluation of medium- and long-term consequences, and rational planning for the future are of no use. The condition of dependence and extreme vulnerability requires an ethics that places responsibility and the quality of relationship at the center of moral discourse Care Ethics welcomes responsibility as an ethical orientation, but within an overall perspective based on empathic capacity, emotional perception and recognition of the identity and inner world of the other. It is an expression of the humanization process of medicine that aims to care for the patient beyond the possibility of cure.